KRITIK GLOBALISASI: MARAKNYA KONTEN LGBT DALAM MEDIA SOSIAL TIKTOK MENURUT AGAMA DAN HAM - Jazilia Hikmi Nur Aqidah (Universitas Merdeka Madiun, 2022)
Globalization was initially considered to have a positive impact on society in various fields of life. But in reality, globalization also has an impact that affects the mindset, behavior, and socio-cultural life of the community. TikTok is a social media that is loved by the people of Indonesia. One of the things that has shocked TikTok social media is the rise of LGBT content. The presence of LGBT content raises various views and influences for TikTok social media users. This study uses a descriptive qualitative method that provides a description, describes, explains, or describes a complex situation. Data collection techniques in this study used online questionnaires and used books, journal articles and other literatures that were coherent with the objects of discussion. Based on the results of the study, it was found that the rise of LGBT content or the content of LGBT creators will affect the mindset of the community that LGBT is not a deviant behavior and will be normalized. If LGBT behavior is normalized, it will damage the social order of society and threaten the existence of human existence itself. In religious teachings, both Islam and Christianity strongly oppose LGBT behavior. Meanwhile, in human rights, the implementation of human rights must be in accordance with the values ??of Pancasila and the law in Indonesia. The fulfillment of rights will always be limited by the rights of others as well. So the behavior of LGBT is very contrary to the values ??of Pancasila